An 8-week Vitamin D3–fortified fruit drink supplementation increases serum ferritin concentration: a randomized controlled trial in Malaysian women with low iron stores - Suhaimi, Nursyafiqah Aqilah; Loh, Su Peng; Ab. Manan, Norhafizah; Zalbahar, Nurzalinda; Mohamad Alwi, Muhammad Najib; Ahmad Fuzi, Salma Faeza (Elsevier, 2024)
Background: There is limited randomized controlled trial evidence to support the association between vitamin D deficiency and anemia risk, highlighting the necessity for further investigations into the role of vitamin D in influencing iron status. Objective: The aim of this study was to determine the effect of vitamin D3–fortified fruit drink consumption (4,000 IU) on vitamin D and iron status biomarkers among iron-deficient women (serum ferritin of <20 μg/L [to convert μg/L ferritin to ng/mL, multiply by 1]). Design: An 8-week double-blind randomized controlled trial was conducted. Subjects/setting: A total of 45 healthy, nonpregnant, nonlactating subjects aged 18 through 40 years (mean [SD] 25.3 [4.6] years) were included in the study, excluding those who donated blood 6 months prior, regularly consumed nutritional supplements, or had gastrointestinal or iron metabolic disorders. Intervention: Subjects were randomly assigned to receive either vitamin D3–fortified fruit drink or a placebo. Main outcome measures: Measurements of 25-hydroxyvitamin D (25[OH]D), serum ferritin, high-sensitivity C-reactive protein, and full blood count concentrations were obtained at baseline, interim, and post intervention. Statistical analyses: A mixed model, repeated measures analysis of variance was used to analyze the intervention effect. Results: Attrition rate for the study was 13%, with 6 dropouts, and 39 subjects completed the study. Daily consumption of vitamin D3–fortified fruit drink in the intervention group resulted in significant increases in 25(OH)D and serum ferritin concentrations compared with the placebo group. The intervention group showed significantly higher mean (SD) changes (Δ) in both 25(OH)D (Δ 76.4 [30.2] nmol/L [to convert nmol/L 25(OH)D to ng/mL, multiply by .4] vs Δ –1.3 [10.7] nmol/L; P = .001) and serum ferritin concentrations (Δ 2.2 [4.2] μg/L vs Δ –0.3 [3.4] μg/L; P = .048) between baseline and post intervention. The other iron status biomarkers were not affected by the intervention. Conclusions: Our study found that daily vitamin D3–fortified fruit drink supplementation for 8 weeks effectively improved 25(OH)D and iron stores, indicated by increased serum ferritin concentrations, in iron-deficient women. Further research is needed to evaluate its safety, efficacy, feasibility, and optimal food fortification in diverse populations. © 2024 Academy of Nutrition and Dietetics